Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/cancers11060884
|View full text |Cite
|
Sign up to set email alerts
|

Loss of PTEN in Fallopian Tube Epithelium Results in Multicellular Tumor Spheroid Formation and Metastasis to the Ovary

Abstract: High-grade serous ovarian cancer (HGSOC) can originate in the fallopian tube and then spread to the ovary. Our objective was to evaluate the role of multicellular tumor spheroids (MTS) in ovarian metastasis. By testing a panel of murine oviductal epithelial (MOE) cells with genetic alterations mimicking those seen in HGSOC, we found that loss of PTEN allowed MTS formation under ultra-low adhesion conditions. Confirming these results in vivo, MTS-like structures were observed in the oviducts of PAX8Cre/+ PTENfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 51 publications
(92 reference statements)
2
11
0
Order By: Relevance
“…The loss of PTEN functions impairs different key biological processes, ranging from inhibition of cell growth, proliferation, and migration, to promotion of apoptosis and tumor suppressor activity [23], findings that closely resemble our preclinical data. Relevant to our in vitro findings is also the observation that loss of PTEN in fallopian tube epithelium results in multicellular tumor spheroid formation and metastasis to ovary [35].…”
Section: Discussionsupporting
confidence: 75%
“…The loss of PTEN functions impairs different key biological processes, ranging from inhibition of cell growth, proliferation, and migration, to promotion of apoptosis and tumor suppressor activity [23], findings that closely resemble our preclinical data. Relevant to our in vitro findings is also the observation that loss of PTEN in fallopian tube epithelium results in multicellular tumor spheroid formation and metastasis to ovary [35].…”
Section: Discussionsupporting
confidence: 75%
“…Human fallopian tube cells transformed in vitro produce tumours that are morphologically and genetically similar to HGSOC [15][16][17]. Genetically engineered mouse OC models containing mutations commonly found in HGSOC such as p53, PTEN, BRCA1, BRCA2, and Rb1 in tubal secretory cells have shown the phenotype of STIC formation and emergence of HGSOC [18][19][20]. Clinical studies have confirmed that the majority of women who undertook salpingo-oophorectomy due to the presence of BRCA1, 2 mutations had STICs in the fallopian tube.…”
Section: Different Origins Of Ocmentioning
confidence: 98%
“…Moreover, it was recently shown that the loss of PTEN allows the fallopian tube epithelia to form multicellular tumour spheroids, which survive better under ultra-low adhesion conditions, attach to the extracellular matrix exposed during ovulation, and colonize the ovary maybe contributing to seeding of the ovary in high grade serous OC patients [32].…”
Section: Ovarian Cancermentioning
confidence: 99%